Controlling Peat Soil Degradation In Oil Palm Plantations With Applications Mucuna Bracteata In Pt. Jatimjaya Perkasa - M .Ridha Pahlipi; Wawan Wawan; Hapsoh Hapsoh (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2022)
Peatland degradation occurs because of the activities carried out on the land. This study aims to determine the effectiveness of Mucuna bracteata in controlling peat soil degradation in oil palm plantations and the effect of Mucuna bracteata age on peat soil degradation in oil palm plantations. This research was conducted by the survey method. The determination of the research location is done by a purposive sampling method. The type of location is peatland planted with oil palm and applied with Lagume Cover Crop Mucuna bracteata (LCC MB) without LCC MB aged 3, 4, and 5 years. Each location was studied with four replications. The soil physical properties and soil chemical properties (pH, C-organic, N-total, P-available, K-total, CaO, ash content, electrical conductivity, and redox potential) were measured. Peatland planted with oil palm and LCC MB applied was able to control the degradation of physical properties (air holding capacity and volume of weight) and chemical properties (ash content, N-total, P-available, K-total pH, and CaO) compared to those not applied. LCC MB. Peatland planted with oil palm and applied to LCC MB until the age of 3 years was able to control the chemical properties (P-available and K-total), but further increases in the age of LCC MB (4 and 5 years) were no longer effective in controlling the properties of the peat soil. Peatland planted with oil palm and applied to LCC MB was able to control the chemical properties (electrical conductivity and ash content), up to the age of 4 years, but a further increase in the age of LCC MB (5 years) was no longer effective in controlling the properties of the peat soil because it no longer experienced intensive growth.